2019
DOI: 10.1097/pas.0000000000001183
|View full text |Cite
|
Sign up to set email alerts
|

Spindle and Round Cell Sarcoma With EWSR1-PATZ1 Gene Fusion

Abstract: The evolving classification of round cell sarcomas is driven by molecular alterations. EWSR1-PATZ1 fusion positive spindle and round cell sarcoma is one such new tumor entity. Herein, we report two EWSR1-PATZ1 fusion positive spindle and round cell sarcomas with overlapping histological features and polyphenotypic differentiation. The intraabdominal tumors affected female patients, 31 and 53-year-old. Both tumors showed sheets and nests of round to spindle cells, fine chromatin, tiny conspicuous nucleoli, mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 33 publications
0
47
1
2
Order By: Relevance
“…As previously mentioned, these tumors can have a desmoplastic stroma and show polyphenotypic differentiation with desmin positivity, and would also be positive for EWSR1 gene rearrangement by break‐apart FISH. Intra‐abdominal sarcomas with EWSR1 ‐ PATZ1 gene fusion have also shown similar histologic features and immunostaining results, and similarly would show an EWSR1 rearrangement by break‐apart FISH .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…As previously mentioned, these tumors can have a desmoplastic stroma and show polyphenotypic differentiation with desmin positivity, and would also be positive for EWSR1 gene rearrangement by break‐apart FISH. Intra‐abdominal sarcomas with EWSR1 ‐ PATZ1 gene fusion have also shown similar histologic features and immunostaining results, and similarly would show an EWSR1 rearrangement by break‐apart FISH .…”
Section: Discussionmentioning
confidence: 73%
“…Desmin positivity, in the context of a polyphenotypic immunoprofile and particularly if there is a globular staining pattern , is highly suggestive of a DSRCT diagnosis. However, a polyphenotypic immuneprofile with desmin positivity is not specific to DSRCT, and can also be encountered in angiomatous fibrous histiocytoma, intracranial myxoid mesenchymal tumors and sarcomas with EWSR1‐PATZ1 gene fusion . We encountered two such cases while establishing our DSRCT study cohort, which were desmin‐positive but demonstrated an EWSR1‐ATF1 gene fusion on molecular evaluation, one of these cases also had a prominent desmoplastic stroma.…”
Section: Discussionmentioning
confidence: 96%
“…Chromosome 22specific inversions that translocate the transcription factor EWSR1 with PATZ1 have been observed in various sarcomas. While EWSR1 translocates with ETS family proteins in Ewing's sarcoma, it potentially encodes two fusion proteins EWSR1-PATZ1 and PATZ1-EWSR1, the latter of which will contain the BTB domain (Siegfried et al, 2019;Bridge et al, 2019;Chougule et al, 2019;Sankar & Lessnick, 2011;Mastrangelo et al, 2000;Im et al, 2000). The dimerization and co-repressor interaction properties of PATZ1 identified in this study may shed light on the mechanism of these sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…6 To our knowledge, only 15 cases of non-brain EWSR1-PATZ1 fusion sarcomas have been reported (Table II). 2,[7][8][9] No previous report has detailed the presentation, imaging, and treatment course of an EWSR1-PATZ1 sarcoma of the head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…7 Only two prior cases of this variant have been reported in the head and neck since 2000, but in brief as part of a case series. 2,[7][8][9] Thus, we provide a detailed report of the presentation, workup, and management of a new case of ESWR1-PATZ1 sarcoma of soft tissue neck origin.…”
Section: Introductionmentioning
confidence: 99%